Ludwig Wittgenstein and Observaciones a los cuadernos de Gramsci: A Philosophical Fiction - Rivera, Silvia Adriana (Rastros Rostros, 2015)
Purpose: this article is an exercise of “fantastical philosophy” in which the writing of an imagined book —Observaciones a los Cuadernos de Gramsci— is conceived. Topics: from the elusive space of confines and borders —between literature and philosophy, reality and fiction, need and possibility—, a text that facilitates the encounter of two thinkers —Wittgenstein and Gramsci— is rebuilt. Development: perhaps a nonexistent, but not at all impossible encounter. An encounter that allows to re-define Wittgenstein’s work from the marks that Gramsci’s reading gives to his traditional concern for language, directing therapeutic philosophy towards a theory of praxis.Conclusions: thus, the range of alternatives that Wittgenstein bequeathed is enriched, especially in the field of social theory, which has expanded upon being invested by a frank ethical-political commitment.
Keywords: philosophical fiction; philosophy of praxis; ludwig wittgenstein